THE EFFECT OF HIGH PERFORMANCE WORK SYSTEM ON EMPLOYEE SERVICE PERFORMANCE AND OCB WITH RESILIENCE AS A MODERATOR VARIABLE IN PT PERKEBUNAN NUSANTARA III (PERSERO) MEDAN - Salman Farisi; Yudi Siswadi; Jufrizen Jufrizen; Saidan Sany Lubis; Nurhayati Nurhayati (SULTANIST: Jurnal Manajemen dan Keuangan, 2026)
The purpose of this research is to determine the influence of the High Performance Work System on Employee Service Performance and OCB with Resilience as a Moderator Variable at Pt Perkebunan Nusantara Iii (Persero) Medan, both directly and indirectly. This research uses a quantitative approach and statistical analysis, namely partial least squares – structural equestion model (PLSSEM) which aims to carry out path analysis with latent variables. The research results show that the High Performance Work System (HPWS) has a significant and influential effect on Employee Service Performance at PT Perkebunan Nusantara III (Persero) Medan. High Performance Work System (HPWS) has a significant and influential effect on Organizational Citizenship Behavior (OCB) at PT Perkebunan Nusantara III (Persero) Medan. High Performance Work System (HPWS) has a significant and influential effect on Resilience at PT Perkebunan Nusantara III (Persero) Medan. Resilience has a significant influence on Employee Service Performance at PT Perkebunan Nusantara III (Persero) Medan. Resilience has a significant and influential effect on Organizational Citizenship Behavior (OCB) at PT Perkebunan Nusantara III (Persero) Medan.